BIAS ORIENTALISME DALAM JURNALISME TELEVISI: KRITIK ATAS REPRESENTASI PESANTREN DI MEDIA MAINSTREAM - Anjaha Naufal Muhammad; Wifdatun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the manifestation of internal orientalism bias in Indonesian television journalism, with a focus on how pesantren (Islamic boarding schools) are systematically misrepresented by urban-centric mainstream media. Using Critical Discourse Analysis (CDA) and framing analysis as the primary methodological frameworks, this research critically investigates the controversy surrounding TRANS7's program "Xpose Uncensored" (aired October 13, 2025), which triggered widespread protests from thousands of santri (Islamic students) and drew formal sanctions from the Indonesian Broadcasting Commission (KPI) following its distorted portrayal of Pondok Pesantren Lirboyo and its religious leader, KH Anwar Manshur. Drawing on Edward Said's theory of orientalism and Stuart Hall's , encoding/decoding model, this study argues that Indonesian television journalism reproduces a form of internal orientalism, wherein urban media elites position themselves as the rational, modern subject while constructing pesantren as an exotic, feudalistic, and suspicious Other. The findings reveal that rating-driven logic and the commodification of religious symbols lead to the systematic violation of journalistic principles, including balance, accuracy, and cultural sensitivity. The study further demonstrates that the pesantren community's organized resistance, manifested through social media boycotts and legal actions, constitutes a form of oppositional reading that challenges mainstream media's narrative dominance. This research concludes that meaningful reform in Indonesian broadcasting ethics requires not only regulatory enforcement by KPI but also a fundamental epistemological shift in how journalists perceive and report on religiously and culturally distinct communities. Keywords: orientalism bias, television journalism, pesantren representation, media framing, critical discourse analysis, Indonesian broadcasting ethics